Behavioural and metabolic risk factors for mortality from colon and rectum cancer: Analysis of data from the Asia-Pacific Cohort Studies collaboration - Morrison, D.; Parr, C.; Lam, T.; Ueshima, H.; Kim, H.; Jee, S.; Murakami, Y.; Giles, G.; Fang, X.; Barzi, F.; Batty, G.; Huxley, Rachel; et al. (2013)
Background: Colorectal cancer has several modifiable behavioural risk factors but their relationship to the risk of colon and rectum cancer separately and between countries with high and low incidence is not clear. Methods: Data from participants in the Asia Pacific Cohort Studies Collaboration (APCSC) were used to estimate mortality from colon (International Classification of Diseases, revision 9 (ICD-9) 153, ICD-10 C18) and rectum (ICD-9 154, ICD-10 C19-20) cancers. Data on age, body mass index (BMI), serum cholesterol, height, smoking, physical activity, alcohol and diabetes mellitus were entered into Cox proportional hazards models. Results: 600,427 adults contributed 4,281,239 person-years follow-up. The mean ages (SD) for Asian and Australia/New Zealand cohorts were 44.0 (9.5) and 53.4 (14.5) years, respectively. 455 colon and 158 rectum cancer deaths were observed. Increasing age, BMI and attained adult height were associated with increased hazards of death from colorectal cancer, and physical activity was associated with a reduced hazard. After multiple adjustment, any physical activity was associated with a 28% lower hazard of colon cancer mortality (HR 0.72, 95%CI 0.53-0.96) and lower rectum cancer mortality (HR 0.75, 95%CI 0.45-1.27). A 2cm increase in height increased colon and all colorectal cancer mortality by 7% and 6% respectively. Conclusions: Physical inactivity and greater BMI are modifiable risk factors for colon cancer in both Western and Asian populations. Further efforts are needed to promote physical activity and reduce obesity while biological research is needed to understand the mechanisms by which they act to cause cancer mortality.